Fe-capsaicin nanozyme attenuates sepsis-induced acute lung injury by regulating the functions of macrophages - Wang, Ruijie; Zhou, Ning; Xue, Jinfang; Li, Yan; Wang, Yang; Zhu, Huadong; Lv, Chuanzhu (Frontiers in Bioengineering and Biotechnology, 2024)
Background: In sepsis, the lung is one of the worst affected organs, often leading to acute lung injury (ALI).More and more evidence suggests that macrophages are also involved in the pathogenesis of ALI. In our previous study, we successfully synthesized Iron-capsaicin-based nanoparticles (Fe-CAP NPs) and found that it could inhibit the secretion of inflammatory cytokines to alleviate ALI. Here, we further explore the anti-inflammatory mechanism of Fe-CAP NPs.Methods: Bone marrow-derived macrophages (BMDM) and C57 mice were divided into four groups: control group, lipopolysaccharide (LPS) group, CAP+LPS group and Fe-CAP+LPS group. Western blot and Immunofluorescence were used to detect the expression of macrophage phenotypic markers CD86 and CD206 in BMDM and lung tissue. Fluorescence microbeads, Transwell and ROS kit were used to detect the phagocytosis, migration and ROS clearing capability of BMDM. Western blot was used to detect the expression of JAK2/STAT3 pathway and apoptosis proteins in BMDM. TUNEL kit and H&E staining were used to evaluate apoptosis and pathological changes in lung tissue.In vitro, CD86 expression was increased in LPS, but decreased after Fe-CAP pretreatment. CD206 expression was the opposite. Fe-CAP reduced phagocytosis, migration and scavenged ROS in LPS-treated BMDM. Fe-CAP inhibited P-JAK2 and P-STAT3 expression and reduced apoptosis. In vivo, Fe-CAP improved lung histopathology and reduced apoptosis in lung tissue of LPS group. CD86 expression was increased in lung tissue of LPS group, but decreased in Fe-CAP preconditioning, and CD206 expression was reversed.Fe-CAP NPs could alleviate sepsis-induced ALI by regulating the polarization and function of macrophages, reducing ROS level and apoptosis.